PS02.250: PREEMPTIVE ENDOSCOPIC VACUUM DRAINAGE TO PREVENT ANASTOMOTIC LEAKAGE IN UPPER-GI SURGERY: A GAME-CHANGING TECHNOLOGY?. (5th March 2019) - Schmidt, Henner M; Vetter, Diana; Gubler, Christoph; Valli, Piero; Morell, Bernhard; Raptis, Dimitri A; Gutschow, Christian A
Abstract: Background: Anastomotic leak (AL) remains a major cause of morbidity in upper-GI surgery. In many centers, endoluminal vacuum drainage (EVD) has become the mainstay of therapy for AL after esophageal and gastric resections. A new idea is to use the EVD technology in a preemptive setting. In this context, we present a case series of patients that received PEVD upon completion of the anastomosis during esophago-gastric surgery. Methods: Intraoperative PEVD was performed in 10 consecutive patients undergoing minimally invasive esophagectomy with cervical (n = 1) or high intrathoracic (n = 6) anastomosis, and open transhiatally extended (n = 1) or minimally invasive (n = 2) total gastrectomy. The EVD device was removed after three to six (mean 4) days, and the anastomosis was endoscopically inspected for ischemia and AL. Additional contrast radiography, computed tomography, or gastroscopy to exclude AL was performed in seven patients. Primary endpoints in this retrospective series was AL; secondary endpoints were the postoperative morbidity measured by the Clavien-Dindo (CD) classification and the comprehensive complication index (CCI), all at 30 days after surgery. Results: Perioperative mortality was 0% with uneventful anastomotic healing in all patients of this series (AL rate 0%, anastomotic stenosis 0%). There were no adverse events attributable to PEVD. None of the patients experienced major morbidity (> CD grade IIIa) during the postoperative course. The median postoperative ICU and hospital stay was 1 (IQR 1-1.75) and 14 (IQR 12-16) days, respectively. Five patients (50%) developed at least one complication, mostly related to infection (2 patients) and pulmonary events (2 patients). The mean CCI at 30 days after surgery was 13.7 (range 0-39.5). Conclusion: PEVD appears to be a safe procedure that may emerge as a groundbreaking technology in patients undergoing esophageal or gastric resection. Further research is needed to elucidate the true potential of this technique. Disclosure: All authors have declared no conflicts of interest.